Search and Comparison of Isim Ma'rifat with Remove Diacritic in the Qur'an and Hadith of Abu Daud - Teuku Muhammad Ikhsan; Eko Darwiyanto; Moch Arif Bijaksana (Journal of Computer System and Informatics (JoSYC), 2023)
This research aims to address the issues of searching for and comparing Isim Ma'rifat (definite nouns) with the prefix "AL" (ال) in the Quran and Hadith Abu Daud. Accurate sources of information regarding nouns in Islam are crucial, and the sayings of the Prophet (Hadith) serve as the primary reference for explaining Isim Ma’rifat. The Remove Diacritics method allows the removal of punctuation marks in the Arabic language, facilitating the search for Isim Ma'rifat with the prefix "AL" (ال) in both sources. The primary objective of this study is to evaluate the ability of Hadith Abu Daud to explain the Isim Ma'rifat found in the Quran. The comparison results reveal 376 instances of identical Isim Ma'rifat between the Quran and Hadith Abu Daud. Additionally, there are 611 instances of Isim Ma'rifat found solely in the Quran and 1388 instances found exclusively in Hadith Abu Daud. These findings provide insights into the capacity of Hadith Abu Daud to explain Isim Ma'rifat in the Quran. The search and comparison of Isim Ma'rifat in the Quran and Hadith Abu Daud hold significant contributions to the development of Quranpedia. Valid information about Isim Ma'rifat and the comparisons between the Quran and Hadith Abu Daud can enrich the content on Quranpedia. In creating the Quranpedia website, the search results for Isim Ma'rifat offer accurate information about nouns mentioned in the Quran, aiding users in better understanding the meanings and uses of Isim Ma'rifat in the religious context. The comparison between the Quran and Hadith Abu Daud provides insights into Hadith Abu Daud's ability to explain Isim Ma'rifat in the Quran. This information can be presented as articles or comparisons to enrich users' knowledge about the relationship between the Quran and hadith concerning the use of nouns in Islam.